A dual-element doped P2 type sodium ion battery positive electrode material, a preparation method and application thereof

CN122889738APending Publication Date: 2026-10-09GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611305217.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

其次,Na⁺/空位有序化与Jahn-Teller效应严重迟滞了钠离子的扩散动力学:前者在层内形成有序排列阻塞离子迁移通道,后者则因Mn³⁺(由部分Mn4⁺还原产生)导致过渡金属氧八面体畸变,进一步增加了离子迁移阻力

Benefits of technology

本发明提供的这种双元素掺杂P2型钠离子电池正极材料,选择Li和Zn共掺杂改性,其中,Li发挥电子结构调控作用,占据TM位点以调节TM-O共价性并提升氧空位形成能,从热力学上抑制晶格氧的不可逆流失,同时Zn发挥结构支撑锚定功能,通过形成更强的Zn-O键锚定TMO2层,从动力学上阻断TM层滑移路径以抑制P2-O2相变,且低化合价掺杂促使Mn价态升高以减少Mn³⁺含量,从而削弱Jahn-Teller效应并减轻结构畸变,最终使复杂的多相变反应机制向单相固溶体反应机制转变,不仅消除了相界面迁移能垒并优化Na⁺扩散动力学以赋予超高倍率性能,还通过扩大层间距拓宽钠离子通道进一步提升传输效率,从而在牺牲少量容量的前提下显著增强材料的循环稳定性和电化学可逆性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889738A_ABST
    Figure CN122889738A_ABST
Patent Text Reader

Abstract

The application provides a double-element doped P2-type sodium ion battery positive electrode material and a preparation method and application thereof. 0.67 Li x Zn y Mn 0.67 Ni 0.33‑x‑y O2, wherein 0.02<=x<=0.04 and 0.06<=y<=0.09. In the application, Li plays an electron structure regulating role, occupies TM sites to adjust TM-O covalence and improves oxygen vacancy formation energy, and inhibits irreversible loss of lattice oxygen. Meanwhile, Zn plays a structure support anchoring function, forms a stronger Zn-O bond to anchor TMO2 layers to block TM layer slip paths and inhibit P2-O2 phase transition. Low valence doping promotes the increase of Mn valence to reduce the content of Mn3+, weakens the Jahn-Teller effect and reduces structural distortion. Finally, the complex multi-phase transition reaction mechanism is changed to a single-phase solid solution reaction mechanism, not only eliminating the phase interface migration energy barrier and optimizing Na+ diffusion kinetics to give super-high rate performance, but also widening the sodium ion channel by expanding the layer spacing to further improve the transmission efficiency, thereby significantly enhancing the cycle stability and electrochemical reversibility of the material under the premise of sacrificing a small amount of capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery material technology, specifically relating to a dual-element doped P2-type sodium-ion battery cathode material, its preparation method, and its application. Background Technology

[0002] With the continued growth in global demand for renewable and clean energy, and the increasing prominence of price increases and supply security issues caused by the overexploitation of lithium resources, developing next-generation low-cost, high-safety electrochemical energy storage systems has become an urgent task in the energy sector. Sodium-ion batteries (SIBs), due to their abundant resources, uniform distribution, low cost, and high similarity to lithium-ion batteries in their working principle, are considered one of the most promising alternatives for large-scale energy storage and low-speed electric vehicles. Among numerous cathode material systems, P2-type layered transition metal oxides (NaxTMO2) have attracted widespread attention from researchers due to their excellent sodium-ion diffusion kinetics imparted by their open triangular prism channels, high theoretical specific capacity, and simple synthesis process.

[0003] Among them, P2-Na 0.67 Mn 0.67 Ni 0.33 O2 (NNM) is one of the most representative materials in this system. It is synthesized through Ni²⁺ / Ni³⁺ / Ni 4 The multi-electron redox reaction of ⁺ provides charge compensation, enabling higher discharge specific capacity and operating voltage. Furthermore, its fabrication process is highly compatible with lithium-ion battery layered oxides, demonstrating promising application prospects.

[0004] However, the electrochemical performance of P2-NNMO in practical applications has fallen far short of theoretical expectations, and its commercialization is hampered by a series of thorny issues. First, the high-voltage detrimental phase transition is a core bottleneck: when charged to high voltages (>4.2 V), a large number of sodium ions are released, leading to strong electrostatic repulsion between adjacent oxygen layers, inducing an irreversible interlayer slip phase transition from the P2 structure to the O2 structure, accompanied by a huge volume change of approximately 20%, causing particle cracking and structural collapse. Second, Na⁺ / vacancy ordering and the Jahn-Teller effect severely impede the diffusion kinetics of sodium ions: the former forms an ordered arrangement within the layers, blocking ion migration channels, while the latter, due to Mn³⁺ (partially composed of Mn...), hinders the diffusion of sodium ions. 4 The reduction of oxygen (⁺) leads to octahedral distortion of the transition metal, further increasing ion migration resistance. Furthermore, interfacial side reactions and transition metal dissolution at high voltages, along with the material's intrinsic air sensitivity (hygroscopicity), severely deteriorate electrode / electrolyte interface stability and the material's storage and processing performance. These issues ultimately result in poor cycling stability, insufficient rate performance, and severe capacity decay at high voltages for P2-NNMO. Summary of the Invention

[0005] This invention provides a dual-element doped P2-type sodium-ion battery cathode material that exhibits excellent stability over a wide voltage range and has ultra-high rate performance.

[0006] Therefore, the technical solution provided by the present invention is as follows: A dual-element doped P2-type sodium-ion battery cathode material with the chemical formula Na 0.67 Li x Zn y Mn 0.67 Ni 0.33-x -y O2, where 0.02 ≤ x ≤ 0.04, 0.06 ≤ y ≤ 0.09.

[0007] Furthermore, its chemical formula is Na. 0.67 Li 0.02 Zn 0.06 Mn 0.67 Ni 0.25 O2, Na 0.67 Li 0.04 Zn 0.06 Mn 0.67 Ni 0.2 3O2, Na 0.67 Li 0.04 Zn 0.09 Mn 0.67 Ni 0.20 O2.

[0008] This invention addresses the limitations of existing cathode materials such as Na. 0.67 Ni 0.33 Mn 0.67 O2 is improved by doping with Li and Zn. Li plays a role in electronic structure regulation, occupying TM sites to adjust TM-O covalentity and increase oxygen vacancy formation energy, thus thermodynamically suppressing irreversible loss of lattice oxygen. Meanwhile, Zn provides structural support and anchoring, forming stronger Zn-O bonds to anchor the TMO2 layer, kinetically blocking the TM layer slip path to suppress the P2-O2 phase transition. Furthermore, low-valence doping promotes an increase in the valence state of Mn, thereby reducing Mn content. 3+ The content of sodium ions is reduced, thereby weakening the Jahn-Teller effect and mitigating structural distortion. Ultimately, the complex multiphase reaction mechanism is transformed into a single-phase solid solution reaction mechanism. This not only eliminates the phase interface migration energy barrier and optimizes the Na⁺ diffusion kinetics to endow it with ultra-high rate performance, but also further improves the transport efficiency by widening the sodium ion channels through increasing the interlayer spacing. Thus, the cycling stability and electrochemical reversibility of the material are significantly enhanced without sacrificing a small amount of capacity.

[0009] This invention also provides a method for preparing a dual-element doped P2-type sodium-ion battery cathode material, comprising the following steps: Step 1) According to the chemical formula Na 0.67 Li x Zn y Mn 0.67 Ni 0.33-x -y The molar ratio of each element in O2 is determined by adding the corresponding amounts of metal salts NiC4H6O4, MnC4H6O4, ZnC4H6O4, LiC2H3O2, and NaC2H3O2 to deionized water and stirring until homogeneous to obtain a mixed metal salt solution. Step 2) Add oxalic acid solution to the mixed metal salt solution to adjust the pH to 1-3, and stir at room temperature for 14-16 hours; Step 3) Place the stirred liquid into an oil bath at 120~130℃ and heat until the water completely disappears to obtain powder; Step 4) The powder is heated and sintered to obtain a dual-element doped P2 type sodium-ion battery cathode material.

[0010] Further, the mass ratio of the metal salt to deionized water in step 1) is 4~7:1.

[0011] Further, in step 2), the mass ratio of anhydrous oxalic acid to water in the oxalic acid solution is 1:30~42.

[0012] Furthermore, the sintering process in step 4) is as follows: First, the powder is transferred to a corundum pot, then pre-sintered, and finally sintered a second time.

[0013] Furthermore, the pre-sintering process is as follows: under an air atmosphere, heat to 500-550℃ and hold for 5-6 hours.

[0014] Furthermore, after pre-sintering, wait for the temperature to drop to room temperature ~ 50℃, then perform a second sintering. In an air atmosphere, heat to 900-950℃ and hold for 10-12 hours. After cooling to below 60℃, remove and store in a glove box.

[0015] This invention also provides the application of a dual-element doped P2-type sodium-ion battery cathode material in the preparation of sodium-ion battery cathodes.

[0016] Furthermore, the positive electrode material, binder, and conductive carbon are added to N-methyl-2-pyrrolidone and mixed evenly to obtain a positive electrode slurry.

[0017] The beneficial effects of this invention are as follows: The dual-element doped P2-type sodium-ion battery cathode material provided by this invention selects Li and Zn co-doping modification. Li plays a role in electronic structure regulation, occupying TM sites to adjust TM-O covalency and increase oxygen vacancy formation energy, thus thermodynamically suppressing irreversible loss of lattice oxygen. At the same time, Zn plays a structural support and anchoring function, anchoring the TMO2 layer by forming stronger Zn-O bonds, thus kinetically blocking the TM layer slip path to suppress the P2-O2 phase transition. In addition, low valence doping promotes the increase of Mn valence state to reduce Mn³⁺ content, thereby weakening the Jahn-Teller effect and reducing structural distortion. Ultimately, it transforms the complex multiphase transition reaction mechanism into a single-phase solid solution reaction mechanism. This not only eliminates the phase interface migration energy barrier and optimizes Na⁺ diffusion kinetics to endow ultra-high rate performance, but also widens the sodium ion channels by increasing the interlayer spacing to further improve transport efficiency. Thus, it significantly enhances the cycle stability and electrochemical reversibility of the material while sacrificing a small amount of capacity. Attached Figure Description

[0018] Figure 1 It is the existing cathode material Na 0.67 Ni 0.33 Mn 0.67 XRD pattern of O2; Figure 2 Na is the embodiment of the present invention 0.67 Ni 0.23 Mn 0.67 Li 0.04 Zn 0.06 XRD pattern of O2; Figure 3 Na is the embodiment of the present invention 0.67 Ni 0.23 Mn 0.67 Li 0.04 Zn 0.06 SEM image of O2; Figure 4 It is the existing cathode material Na 0.67 Ni 0.33 Mn 0.67 Charge and discharge curves of O2; Figure 5 Na is the embodiment of the present invention 0.67 Ni 0.23 Mn 0.67 Li 0.04 Zn 0.06 Charge and discharge curves of O2; Figure 6 These are charge-discharge curves for different electrodes; Figure 7 It is a cyclic curve graph of different magnifications; Figure 8 This is a cyclic curve graph of NNMLZ20C. Detailed Implementation

[0019] The following specific embodiments illustrate the implementation of the invention. Those skilled in the art can easily understand other advantages and effects of the invention from the content disclosed in this specification.

[0020] Exemplary embodiments of the invention are now described with reference to the accompanying drawings. However, the invention may be embodied in many different forms and is not limited to the embodiments described herein. These embodiments are provided to fully and completely disclose the invention and to fully convey its scope to those skilled in the art. The terminology used in the exemplary embodiments illustrated in the drawings is not intended to limit the invention.

[0021] Unless otherwise stated, the terms used herein (including technical terms) have their common meaning as understood by one of ordinary skill in the art. Furthermore, it is understood that terms defined in commonly used dictionaries should be understood to have a meaning consistent with the context of their relevant field, and not to be interpreted as having an idealized or overly formal meaning.

[0022] This invention provides a dual-element doped P2-type sodium-ion battery cathode material with the chemical formula Na. 0.67 Li x Zn y Mn 0.67 Ni 0.33-x -y O2, where 0.04 ≤ x ≤ 0.06, 0.06 ≤ y ≤ 0.09.

[0023] Furthermore, its chemical formula is Na. 0.67 Li 0.02 Zn 0.06 Mn 0.67 Ni 0.25 O2, Na 0.67 Li 0.04 Zn 0.06 Mn 0.67 Ni 0.2 3O2, Na 0.67 Li 0.04 Zn 0.09 Mn 0.67 Ni 0.20 O2.

[0024] Example 1 This embodiment provides a dual-element doped P2-type sodium-ion battery cathode material with the chemical formula Na. 0.67 Li 0.02 Zn 0.06 Mn 0.67 Ni 0.25 O2. The preparation process is as follows: Step 1) Take 7.35 mg of lithium carbonate, 110.0 mg of zinc acetate, 1.64 g of manganese acetate, 622.1 mg of nickel acetate, and 577 mg of sodium acetate by mass ratio and mix them in 200 ml of deionized water. Stir well. Step 2) Add 0.95g of anhydrous oxalic acid to 30ml of deionized water, and slowly add the oxalic acid solution dropwise into the mixed solution while stirring; after the oxalic acid solution and the mixed solution are mixed, continue stirring for 14-16 hours. Step 3) Heat the mixed solution after stirring for 14 hours to 120°C using an oil bath until all the water in the solution is completely evaporated, leaving only powder. Step 4) Transfer the powder to a corundum pot and heat it using a muffle furnace; first, perform pre-sintering by heating to 500°C in air and holding for 5 hours; wait for the temperature to drop to room temperature, then perform secondary sintering by heating to 900°C in air and holding for 10 hours; after cooling to 55°C, remove the powder and store it in a glove box.

[0025] Example 2 This embodiment provides a dual-element doped P2-type sodium-ion battery cathode material with the chemical formula Na. 0.67 Li 0.04 Zn 0.06 Mn 0.67 Ni 0.23 O2. The preparation process is as follows: Step 1) Take 14.7 mg of lithium carbonate, 110.0 mg of zinc acetate, 1.64 g of manganese acetate, 572.3 mg of nickel acetate, and 577 mg of sodium acetate by mass ratio and mix them in 225 ml of deionized water. Stir well. Step 2) Add 0.95g of anhydrous oxalic acid to 30ml of deionized water, and slowly add the oxalic acid solution dropwise into the mixed solution while stirring; after the oxalic acid solution and the mixed solution are mixed, continue stirring for 15 hours. Step 3) Heat the mixed solution after stirring for 15 hours to 125°C using an oil bath until all the water in the solution is completely evaporated, leaving only powder. Step 4) Transfer the powder to a corundum pot and heat it using a muffle furnace; first, perform pre-sintering by heating to 525°C in an air atmosphere and holding for 6 hours; wait for the temperature to drop to 35°C, then perform secondary sintering by heating to 925°C in an air atmosphere and holding for 11 hours; after cooling to 50°C, remove the powder and store it in a glove box.

[0026] Example 3 This embodiment provides a dual-element doped P2-type sodium-ion battery cathode material with the chemical formula Na. 0.67 Li 0.04 Zn0.09 Mn 0.67 Ni 0.20 O2. The preparation process is as follows: Step 1) Take 14.7 mg of lithium carbonate, 165 mg of zinc acetate, 1.64 g of manganese acetate, 497.72 mg of nickel acetate, and 577 mg of sodium acetate by mass ratio and mix them in 250 ml of deionized water. Stir well. Step 2) Add 0.95g of anhydrous oxalic acid to 40ml of deionized water, and slowly add the oxalic acid solution dropwise into the mixed solution while stirring; after the oxalic acid solution and the mixed solution are mixed, continue stirring for 16 hours. Step 3) Heat the mixed solution after stirring for 16 hours to 130°C using an oil bath until all the water in the solution is completely evaporated, leaving only powder. Step 4) Transfer the powder to a corundum pot and heat it using a muffle furnace; first, perform pre-sintering by heating to 550°C in air and holding for 6 hours; wait for the temperature to drop to 50°C, then perform secondary sintering by heating to 950°C in air and holding for 12 hours; after cooling to 40°C, remove the powder and store it in a glove box.

[0027] Comparative Example 1 The chemical formula of the comparative cathode material is Na. 0.67 Mn 0.67 Ni 0.33 O2. The preparation process is as follows: Step 1) Take 1.64g of manganese acetate, 821.2mg of nickel acetate, and 577mg of sodium acetate by mass ratio and mix them in 250ml of deionized water. Stir well. Step 2) Add 0.95g of anhydrous oxalic acid to 40ml of deionized water, and slowly add the oxalic acid solution dropwise into the mixed solution while stirring; after the oxalic acid solution and the mixed solution are mixed, continue stirring for 16 hours. Step 3) Heat the mixed solution after stirring for 16 hours to 130°C using an oil bath until all the water in the solution is completely evaporated, leaving only powder. Step 4) Transfer the powder to a corundum pot and heat it using a muffle furnace; first, perform pre-sintering by heating to 550°C in air and holding for 6 hours; wait for the temperature to drop to 50°C, then perform secondary sintering by heating to 950°C in air and holding for 12 hours; after cooling to 40°C, remove the powder and store it in a glove box.

[0028] To further illustrate the effects of the present invention, the cathode materials of Examples 1-3 and Comparative Example 1 were characterized and applied to batteries for electrochemical testing.

[0029] Existing material Na 0.67 Mn 0.67Ni 0.33 The first peak of O2 (Comparative Example 1) [(002) crystal plane] is located at 15.9°, as shown below. Figure 1 As shown; the positive electrode material Na prepared in Example 2 of this invention 0.67 Li 0.04 Zn 0.06 Mn 0.67 Ni 0.23 The first peak of O2 is located at 15.8°, as... Figure 2 As shown, the (002) crystal plane shifts at a low angle, indicating that the lattice along the c-axis of the material has expanded. This suggests that Zn has been successfully incorporated into the material, affecting its structure, expanding the c-axis, and increasing the interlayer spacing, thus providing structural assurance for excellent rate performance. Figure 3 As shown, the positive electrode material Na prepared in Example 2 of this invention... 0.67 Li 0.04 Zn 0.06 Mn 0.67 Ni 0.23 O2 was scanned by SEM, and the material showed a complete bulk layered structure.

[0030] The cathode materials of Examples 1-3 and the comparative examples were assembled into batteries using the following method: 1) Mix all materials thoroughly in a mass ratio of 1:1:8. For example, with a total mass of 100mg, add 10mg of binder (PVDF), 10mg of conductive carbon (Super P), and 80mg of positive electrode material to 360mg of N-methyl-2-pyrrolidone (NMP) and mix for 2-3 hours. 2) Apply the mixed slurry evenly to the surface of the aluminum foil using a 100µm coater, and then transfer the coated slurry to an 80℃ oven for 8-10 hours. 3) Cut the dried electrode sheets into 12mm diameter round pieces using a cutting machine. Use the cut electrode sheets as the positive electrode, the glass fiber round pieces as the separator, 120ul of electrolyte (a mixed solution of 1 M NaPF6 dissolved in ethylene carbonate (EC) / diethyl carbonate (DEC) (volume ratio 1:1)), and the sodium sheet as the negative electrode to assemble a CR2032 button cell for subsequent electrochemical testing.

[0031] Figure 4 for Na 0.67 Ni 0.33 Mn 0.67The charge-discharge curves of O2 cathode materials exhibit a distinct step-like shape during charging, stemming from a series of complex and discontinuous structural phase transitions occurring during the charging and discharging process. In the initial charging and discharging phases (low voltage region, typically <4.0 V), extracted or inserted Na⁺ and residual Na⁺ in the crystal lattice tend to form a long-range ordered superstructure, i.e., a "Na⁺ / vacancy ordered" arrangement. This ordering process keeps the electrode potential almost constant within a narrow capacity range, macroscopically manifesting as a flat voltage plateau on the charge-discharge curve. As the Na⁺ concentration changes, this ordered structure undergoes multiple reorganizations, forming multiple smaller plateaus, thus creating the step-like curve characteristic.

[0032] When the charging voltage exceeds 4.2V, a large amount of Na⁺ is released, weakening the interlayer electrostatic repulsion and causing the adjacent transition metal layer (TMO₂) to slip. This is a typical two-phase reaction, meaning that a new phase (O₂) nucleates and grows while the old phase (P₂) is gradually consumed, i.e., Na⁺ is released. 0.67 Ni 0.33 Mn 0.67 In O2 cathode materials, lattice oxygen can evolve from a highly reversible O2⁻→O2ⁿ⁻ redox reaction into irreversible O2 generation, leading to lattice oxygen loss and causing transition metals (TM) to lose coordination sites and dissolve, ultimately resulting in structural damage and capacity decay.

[0033] like Figure 5 As shown, the cathode material Na prepared in Example 2, doped with Li and Zn, is... 0.67 Li 0.04 Zn 0.06 Mn 0.67 Ni 0.23 The charging curve of O2 shows a straight line, without a complex phase transition process, corresponding to a single-phase solid solution reaction, meaning that Na⁺ is continuously and uniformly extracted / intercalated. Lattice parameters (such as interlayer spacing) change smoothly and linearly with Na⁺ content, completely avoiding structural abrupt changes. This means that the internal stress of the material is greatly released, and the integrity of the particles is maintained for a long time.

[0034] In the cathode material of this invention, Li plays a role in electronic structure regulation, occupying TM sites to adjust TM-O covalentity and increase oxygen vacancy formation energy, thereby thermodynamically suppressing irreversible loss of lattice oxygen. At the same time, Zn plays a structural support and anchoring function, anchoring the TMO2 layer by forming stronger Zn-O bonds, thereby kinetically blocking the TM layer slip path to suppress the P2-O2 phase transition. Furthermore, low valence doping promotes the increase of Mn valence state to reduce Mn³⁺ content, thereby weakening the Jahn-Teller effect and reducing structural distortion. Ultimately, this transforms the complex multiphase transition reaction mechanism into a single-phase solid solution reaction mechanism. This not only eliminates the phase interface migration energy barrier and optimizes Na⁺ diffusion kinetics to endow ultra-high rate performance, but also further improves transport efficiency by widening sodium ion channels through increased interlayer spacing. Thus, the cycling stability and electrochemical reversibility of the material are significantly enhanced without sacrificing a small amount of capacity.

[0035] Figure 6 In the middle NNML0.02Z0.06, Na is... 0.67 Ni 0.28 Mn 0.67 Li 0.02 Zn 0.06 O2, NNML0.04Z0.06 is Na 0.67 Ni 0.23 Mn 0.67 Li 0.04 Zn 0.06 O2, NNML0.04Z0.09 is Na 0.67 Ni 0.20 Mn 0.67 Li 0.04 Zn 0.09 NNM is Na 0.67 Ni 0.33 Mn 0.67 After 200 cycles at 2.0–4.4 V and 1 C, the capacity retention rates were 66.99%, 86.34%, 91.75%, and 53.90%, respectively. Therefore, doping improves capacity retention.

[0036] like Figure 7 As shown, at 5C, NNMLZ (Na) 0.67 Ni 0.23 Mn 0.67 Li 0.04 Zn 0.06 The discharge specific capacity of O2) reached 95.73 mAh / g, while NNM (Na) 0.67 Ni 0.33 Mn 0.67 The O2 content is only 9.13 mAh / g, indicating that NNMLZ has excellent rate performance.

[0037] like Figure 8 As shown, Na in Comparative Example 1 0.67 Ni 0.33 Mn 0.67 O2 (NNM) lacks high-rate charge / discharge performance; its charge / discharge capacity is 0 at 20C. Na 0.67 Ni 0.23 Mn 0.67 Li 0.04 Zn 0.06 At a rate of 20C, O2(NNMLZ) has a first-cycle discharge capacity of 91mAh / g and a capacity retention rate of 71% after 1000 cycles.

[0038] In summary, the cathode material of this invention exhibits excellent stability over a wide voltage range and possesses extremely high rate performance. At 4.4V-2.0V and 20C, the specific capacity of the first cycle is 91.7mAh / g, and the retention rate is 71% after 1000 cycles.

[0039] The examples above are merely illustrative of the invention and do not constitute a limitation on the scope of protection of the invention. Any design that is the same as or similar to the invention falls within the scope of protection of the invention.

Claims

1. A dual-element doped P2-type sodium-ion battery cathode material, characterized in that, Its chemical formula is Na 0.67 Li x Zn y Mn 0.67 Ni 0.33-x -y O2, where 0.02 ≤ x ≤ 0.04, 0.06 ≤ y ≤ 0.

09.

2. The dual-element doped P2-type sodium-ion battery cathode material according to claim 1, characterized in that, Its chemical formula is Na 0.67 Li 0.02 Zn 0.06 Mn 0.67 Ni 0.25 O2, Na 0.67 Li 0.04 Zn 0.06 Mn 0.67 Ni 0.23 O2, Na 0.67 Li 0.04 Zn 0.09 Mn 0.6 7Ni 0.20 O2.

3. A method for preparing the dual-element doped P2-type sodium-ion battery cathode material according to claim 1 or 2, characterized in that, Includes the following steps: Step 1) According to the chemical formula Na 0.67 Li x Zn y Mn 0.67 Ni 0.33-x -y The molar ratio of each element in O2 is determined by adding the corresponding amounts of metal salts NiC4H6O4, MnC4H6O4, ZnC4H6O4, LiC2H3O2, and NaC2H3O2 to deionized water and stirring until homogeneous to obtain a mixed metal salt solution. Step 2) Add oxalic acid solution to the mixed metal salt solution to adjust the pH to 1-3, and stir at room temperature for 14-16 hours; Step 3) Place the stirred liquid into an oil bath at 120~130℃ and heat until the water completely disappears to obtain powder; Step 4) The powder is heated and sintered to obtain a dual-element doped P2 type sodium-ion battery cathode material.

4. The method for preparing a dual-element doped P2-type sodium-ion battery cathode material according to claim 3, characterized in that, The mass ratio of the metal salt to deionized water in step 1) is 4~7:

1.

5. The method for preparing a dual-element doped P2-type sodium-ion battery cathode material according to claim 3, characterized in that, In step 2), the mass ratio of anhydrous oxalic acid to water in the oxalic acid solution is 1:30~42.

6. The method for preparing a dual-element doped P2-type sodium-ion battery cathode material according to claim 3, characterized in that, The sintering process in step 4) is as follows: First, the powder is transferred to a corundum pot, then pre-sintered, and finally sintered a second time.

7. The method for preparing a dual-element doped P2-type sodium-ion battery cathode material according to claim 6, characterized in that, The pre-sintering process is as follows: heat to 500-550℃ in air atmosphere and hold for 5-6 hours.

8. The method for preparing a dual-element doped P2-type sodium-ion battery cathode material according to claim 6, characterized in that, After pre-sintering, wait for the temperature to drop to room temperature ~50℃, then perform a second sintering. In an air atmosphere, heat to 900-950℃ and hold for 10-12 hours. After cooling to below 60℃, remove and store in a glove box.

9. The application of the dual-element doped P2-type sodium-ion battery cathode material as described in claim 1 or 2 in the preparation of sodium-ion battery cathodes.

10. The application of the dual-element doped P2-type sodium-ion battery cathode material according to claim 9 in the preparation of sodium-ion battery cathodes, characterized in that, The positive electrode material, binder, and conductive carbon are mixed evenly in N-methyl-2-pyrrolidone to obtain the positive electrode slurry.